The Phenomenon of Female Defamation on Social Media: An Examination of Hadith on Ghibah and the Ethics of Virtual Interaction - Aini, Mufidatun Nur; Anwar, Latifah (AMK : Abdi Masyarakat UIKA, 2025)
The defamation of women on social media has become an alarming phenomenon, given its potential to harm their dignity and honor. In Islam, preserving the honor of fellow Muslims is an obligation emphasized through the prohibition of ghibah (backbiting). This study aims to understand the phenomenon of defamation against women from the perspective of hadiths on ghibah. This research employs a qualitative approach with a phenomenological method, collecting data through library research on various books and hadith texts. The findings indicate that defamation against women on social media has a significant negative impact on their psychological well-being and social status. These findings align with the principles in the hadiths prohibiting ghibah, making them relevant references for addressing this issue in contemporary times. Ethical social media literacy and moral education programs are essential to reduce the practice of defamation.